The impact of COVID-19 on life expectancy among four Asian American subgroups - Sung S. Park; Noreen Goldman; Hiram Beltrán-Sánchez; Theresa Andrasfay (Elsevier, 2023)
Background and objective: To date, the impact of the COVID-19 pandemic on life expectancy for the Asian American (AA) population has been reported in aggregate. This study provides estimates of life expectancy at birth before and during the pandemic, with a set of demographic, health, and socioeconomic risk factors for the four largest subgroups: Asian Indians, Chinese, Filipinos, and Vietnamese. These estimates are placed in context of the broader U.S. population. Methods: This study uses age-specific all-cause mortality from CDC WONDER and population counts from the American Community Surveys. We apply methodologies to address variability in population sizes over time (smoothing) and data quality issues at older ages (Brass relational model life table system) to produce three sets of sex-specific life expectancy estimates by subgroup for 2019, 2020, and 2021. Results: Almost all estimates show that the four AA subgroups experienced greater losses between 2019 and 2020 than Whites. These losses ranged from 1.1 to 3.9 years, with the largest drops among Chinese women (2.0-2.4) and Filipino men (3.5-3.9). Under all scenarios, losses in life expectancy were considerably smaller in 2021 than in 2020 among the four subgroups - with several subgroups experiencing a modest rebound - but these improvements did not compensate for the large increases in death rates in 2020. Filipino men had the largest decline in life expectancy from 2019 to 2021 among the four subgroups (3.4-4.2 years), and Vietnamese men and women experienced large losses which continued into the second year of the pandemic. Conclusions: Despite high pre-pandemic life expectancies, AAs suffered a large, and rarely acknowledged, increase in mortality during the pandemic, with substantial heterogeneity across subgroups and between women and men. This variability is due in part to the pronounced differences in risk factors for infection and severity which have been documented within the AA population.